IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM PENDIDIKAN KARAKTER DI SD NEGERI 1 TAMBAKREJO: penelitian kualitatif - Annisa Laili Rahmadani; Soegeng Ysh; Wijayanti, Arfilia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background that drives this research is that the implementation of SBM at SD N 1 Tambakrejo looks good and effective, has school quality and adequate facilities and infrastructure. Even though the MBS at this school is considered good, several students have less than desirable characteristics in school and outside school activities. Due to the students' poor character, SD Negeri 1 Tambakrejo implemented SBM in character education. The problem in this research is "How is the implementation of school-based management in character education at SD Negeri 1 Tambakrejo?" and "What are the driving and inhibiting factors for implementing school-based management in character education at SD Negeri 1 Tambakrejo?. The objectives of this research are (1) The process of implementing SBM in character education. (2) Supporting and inhibiting factors for implementing SBM in character education. This research was conducted at SD Negeri 1 Tambakrejo. The subjects of this research were school principals, class teachers, religion teachers, corner teachers, and school committee members. This type of research is qualitative research. The data in this research was obtained from observation, interviews, documentation and questionnaires. The results of this research can be concluded as follows: (1) The SBM implementation process includes 10 indicators of the success of SBM implementation and of the 18 indicators of character education values ​​there are 13 indicators of character education values ​​related to the implementation of school-based management. (2) There are supporting and inhibiting factors in implementing MBS. Based on the results of this research, suggestions that can be made are maintaining the participation of school residents and the community in the school environment in implementing SBM.